Characterization and Neuroprotection Potential of Seleno-Polymannuronate - Bi, Decheng; Li, Xiaofan; Li, Tong; Li, Xiuting; Lin, Zhijian; Yao, Lijun; Li, Hui; Xu, Hong; Hu, Zhangli; Zhang, Zhenqing; Liu, Qiong; Xu, Xu (Frontiers in Pharmacology, 2020)
Seleno-polymannuronate (Se-PM) was prepared from alginate-derived polymannuronate (PM) through a sulfation followed by a selenylation replacement reaction. The organic selenium content of Se-PM was 437.25 μg/g and its average molecular weight was 2.36 kDa. The neuroprotection effect of Se-PM and corresponding molecular mechanisms were investigated. Our results showed that, comparing to both sulfated PM (S-PM) and PM, Se-PM remarkably inhibited the aggregation of Aβ1–42 oligomer in vitro and significantly reduced the APP and BACE1 protein expression in N2a-sw cells, highlighting the critical function of the selenium presented in Se-PM. Moreover, Se-PM decreased the expression of cytochrome c and the ratio of Bax to Bcl-2, and enhanced the mitochondrial membrane potential in N2a-sw cells. These results suggested that Se-PM treatment can markedly inhibit N2a-sw cell apoptosis and promote N2a-sw cell survival and that Se-PM might be a potential therapeutic agent for the prevention of neurodegeneration owing to its remarkable neuroprotection effect.